A Survey Of Facilities and Infrastructure For Physical Education Sports and Health At Junior High Schools In Rambah Samo Sub-District, Rokan Hulu District - Kaputri, Devya Ramela; Putra, Muarif Arhas; Manurizal, Lolia (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
The purpose of this study was to determine how much the availability of Physical Education Sports and Health Facilities and Infrastructure in State Junior High Schools in Rambah Samo District, Rokan Hulu Regency. The method used in this research is the quantitative method. This research was conducted at State Junior High Schools in Rambah Samo District, Rokan Hulu Regency. Data collection is done using observation and documentation. The type of data analysis uses descriptive analysis techniques which are then interpreted descriptive analysis in this study to determine the completeness of physical education facilities and infrastructure for sports and health in State Junior High Schools in Rambah Samo District Rokan Hulu Regency. The results of this study indicate that of the 7 public junior high schools in Rambah Samo District, there is one school that has more PJOK facilities and infrastructure than other schools so the school is in the Excellent category with a percentage of 14.3%. Furthermore, 3 junior high schools are in the good category with a percentage of 42.9%, there are 2 junior high schools in the medium category with a percentage of 28.5% and 1 junior high school in the poor category with a percentage of 14.3%.